Strategi Peningkatan Kinerja Pemasaran Pada Green Entrepreneurship Kursi dan Meja Limbah Bandengan Analisis 4P - Arif Dzulfikar; Busharmaidi; Astriyani Sandya Paramita; Nadia Ayulya Syahrial; Evita Ratna Sari (Jurnal Serambi Engineering, 2024)
The amount of tire waste in Indonesia is estimated to reach 11 million tonnes. One of the businesses that plays a role in preventing environmental damage due to tire waste is Kursi Meja Ban Ciberes business. This business is located in Ciberes, Bogor and processes waste tires into chairs and tables products. This business can be categorized as a green entrepreneurship business The purpose of this study is first to identify and evaluate Product, Price, Place, and Promotion factors. Second, this study aims to develop a strategy on the 4P factors that are considered to require increased performance. Data were collected through interviews with business owners of tire waste table chairs, consumers, business expert, and through obtaining secondary data through literature studies. After being analyzed, two factors were obtained that needed to be improved or increased, the factors are product and promotion. In terms of products, the Kursi Meja Ban Ciberes business can increase the variety of types of tables and chairs it produces, so that it can be in demand by other market segments. From a marketing perspective, marketing content can still be improved with digital marketing. With YouTube marketing content videos and Instagram platform, it is hoped will attract consumers, so that they can increase the number of product sales produced.